(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
This paper aims to analyze the impact of environmental taxes on the reduction of greenhouse gas (GHG) emissions and the generation of fiscal revenues in the 27 European Union (EU) countries during the 2011-2022 period. A quantitative approach was adopted using data from Eurostat and Our World in Data, estimating fixed-effects panel data econometric models. Results reveal a disparity based on the productive context: in less industrialized countries, a 1% increase in environmental taxes is associated with a 0.06% rise in emissions, whereas in more industrialized economies, it leads to a 0.02% decrease. Furthermore, the Environmental Kuznets Curve is validated, identifying a turning point near 31,270 euros of GDP per capita, leading to the conclusion that the effectiveness of these taxes depends on the industrial structure and requires complementary policies for energy transition and fiscal sustainability.